2003
DOI: 10.1063/1.1619948
|View full text |Cite
|
Sign up to set email alerts
|

NO 2 and CO gas adsorption on carbon nanotubes: Experiment and theory

Abstract: In this work a combined experimental and theoretical study on carbon nanotube (CNT) based system for gas sensing applications is reported. Carbon nanotubes thin films have been deposited by plasma-enhanced chemical vapor deposition on Si3N4/Si substrates provided with Pt electrodes. Microstructural features as determined by scanning electron microscopy, transmission electron microscopy, and Raman spectroscopy highlight the growth of defective tubular carbon structures. The electrical resistivity of the CNT fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
141
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(153 citation statements)
references
References 37 publications
7
141
0
5
Order By: Relevance
“…[7] This high affinity for CO over O 2 of hemoglobin and myoglobin is the underlying mechanism of carbon monoxide poisoning in mammals. [8,9] Although detectors for CO are available, there remains a need for massively [16,17] Theoretical and experimental reports have suggested that CO does not engage in charge transfer with pristine SWCNTs, [18][19][20] indicating the a chemical reactive interface is necessary. Conductivity-based CO detection has been reported for carboxylate-containing, [19] deformed, [21] or doped SWCNTs, [22] as well as SWCNTs dispersed in polymers [23] or decorated with metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] This high affinity for CO over O 2 of hemoglobin and myoglobin is the underlying mechanism of carbon monoxide poisoning in mammals. [8,9] Although detectors for CO are available, there remains a need for massively [16,17] Theoretical and experimental reports have suggested that CO does not engage in charge transfer with pristine SWCNTs, [18][19][20] indicating the a chemical reactive interface is necessary. Conductivity-based CO detection has been reported for carboxylate-containing, [19] deformed, [21] or doped SWCNTs, [22] as well as SWCNTs dispersed in polymers [23] or decorated with metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Sensors without iron porphyrin-both pristine (not shown) and functionalized (black curve) SWCNTsshowed negligible responses to CO, which was consistent with the previous reports. [18][19][20]27] Sensors with iron porphyrin showed dosimetric responses indicating irreversibility over the experimental time frame. Pristine SWCNTs (lacking the 4-pyridyl anchor group) when treated with Fe(tpp)ClO 4 (green curve) showed a modest response (−0.57 ± 0.09%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,31,32 Based on the equivalence of the adsorption energy for each combination of the GNRs and BNNRs, 20,33 we used the same probability weight for CO-adsorption on each of the B/N/C sites (similar to Ref. 14).…”
Section: 29-31mentioning
confidence: 99%
“…Atoms, molecules and nanoparticles are some of the objects known to interact strongly with NT, paving their way to being used as nanoscopic sensors [1][2][3][4]. From the theoretical point of view, the problem of which FO produces a good NT-based sensor involves two separate studies: one addressing the conditions under which the FO adheres to the NT, and another investigating the effect that this interaction brings to the electronic properties of the device.…”
Section: Copyright C Epla 2008mentioning
confidence: 99%